2019
DOI: 10.1017/jfm.2019.429
|View full text |Cite
|
Sign up to set email alerts
|

On the emergence of large clusters of acoustic power sources at the onset of thermoacoustic instability in a turbulent combustor

Abstract: In turbulent combustors, the transition from stable combustion (i.e. combustion noise) to thermoacoustic instability occurs via intermittency. During stable combustion, the acoustic power production happens in a spatially incoherent manner. In contrast, during thermoacoustic instability, the acoustic power production happens in a spatially coherent manner. In the present study, we investigate the spatiotemporal dynamics of acoustic power sources during the intermittency route to thermoacoustic instability usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 77 publications
(80 reference statements)
0
32
0
Order By: Relevance
“…The formation of these large-scale vortical structures leads to the coherent production of acoustic power sources over large clusters (Krishnan et al. 2019 b ), as observed in figure 8( c ). A large vortex is also shed from the tip of the bluff body (figure 8 b , at time instant ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The formation of these large-scale vortical structures leads to the coherent production of acoustic power sources over large clusters (Krishnan et al. 2019 b ), as observed in figure 8( c ). A large vortex is also shed from the tip of the bluff body (figure 8 b , at time instant ).…”
Section: Resultsmentioning
confidence: 95%
“…The large-scale vortical structure then convects towards the bluff body (figure 6b at time instants B and C). Recently, Krishnan et al (2019b) have shown that the formation of large-scale vortical structure leads to the conglomeration of acoustic power sources in the flow field. Hence, we observe a coherent acoustic power production during the formation of the vortical structure (figure 6c at time instants A and B).…”
Section: Turbulent Network During Intermittencymentioning
confidence: 99%
See 2 more Smart Citations
“…2017; Krishnan et al. 2019 b ), wall turbulence (Iacobello, Scarsoglio & Ridolfi 2018 b ), mixing in turbulent channel flow (Iacobello et al. 2018 a , 2019 a , b ) and isotropic magnetohydrodynamic turbulence (Gürcan 2018).…”
Section: Introductionmentioning
confidence: 99%